Occurrence of a digenetic trematode in a polychaete - Brown, B; Prezant, R. S. (Journal of Invertebrate Pathology, 1986)
5 citations (Crossref) [2023-10-31]
Keywords: dept.aa

Entrainment of larval oysters by hydraulic cutterhead dredges: An introduction - Prezant, R. S. (Entrainment of Larval Oysters, American Malacological Bulletin, 1986)
Keywords: dept.aa; ⛔ No DOI found

Spiral Crossed-Lamellar Shell Growth in Corbicula (Mollusca: Bivalvia) - Prezant, Robert S.; Tiu, Antonieto Tan (Transactions of the American Microscopical Society, 1986)
Spiral and near-spiral growth patterns of the peripheral crossed-lamellar shell microstructure of the bivalve Corbicula cf. fluminea have been discovered. This is the first report of spiral microstructures outside of nacreous and "foliated calcite" deposits. The spiral growth surface in this corbiculid is underlain by a conical crossed-lamellar microstructure. This form of lath deposition is usually associated with high concentrations of organic material located beneath the undertucked periostracum along the valve's periphery. These structures can offer the bivalve additional resistance against predators that enter the valves through the shell's edge. Similar spiral structures have not been found in all "white" forms of North American Corbicula, in the "purple" form of North American Corbicula, nor in the corbiculids Polymesoda caroliniana and P. (Geloina) erosa.
3 citations (Crossref) [2023-10-31]
Keywords: dept.aa